Within-Season Shift in Fungicide Sensitivity Profiles of Pseudoperonospora cubensis Populations in Response to Chemical Control - Kikway, Isaack (Plant disease, 2023)
Cucurbit downy mildew, caused by Pseudoperonospora cubensis, is an important disease affecting cucurbits worldwide. Chemical control is an effective method for disease control but P. cubensis has a high risk for developing resistance to fungicides. Alternating fungicides with different modes of action is recommended to avoid an increase of resistant subpopulations. Thus, this study was conducted to establish shifts in the sensitivity profiles of P. cubensis isolates during the growing season, wherein chlorothalonil was applied in alternation with either cymoxanil, fluopicolide, or propamocarb in field experiments conducted from 2018 to 2020 at Rocky Mount, NC and in 2018 and 2020 at Charleston, SC. The sensitivity of baseline isolates sampled early in the season or exposed isolates sampled late in the season to these single-site fungicides was determined using a detached-leaf assay, where tested isolates were classified as sensitive or resistant based on the relative disease severity. Based on the Kruskal-Wallis test, the distribution profile of relative disease severity among baseline and exposed isolates was significantly different where chlorothalonil was alternated with fluopicolide (χ2 = 10.82; P = 0.001) but not with cymoxanil (χ2 = 1.39; P = 0.238) or propamocarb (χ2 = 2.37; P = 0.412). Although there was a directional selection toward resistance for isolates sampled from plots that were treated with fluopicolide or propamocarb alternated with chlorothalonil during a growing season, a significant shift in fungicide sensitivity distribution based on combined data were observed for fluopicolide (χ2 = 8.25; P = 0.004) but not propamocarb (χ2 = 1.05; P = 0.461). Baseline and exposed isolates sampled from the cymoxanil-treated plots were all resistant to this fungicide and there was no significant shift in their fungicide sensitivity profile during a growing season (χ2 = 0.06; P = 1.000). These results indicate that a shift toward reduced sensitivity in P. cubensis can occur during a growing season and the efficacy of fluopicolide is likely to decrease as the frequency of the less sensitive subpopulations increases during a production season. The resultant effect on disease severity and selection of an insensitive subpopulation may accelerate the development of resistance to propamocarb in the southeastern United States